A direct catalytic asymmetric Mannich-type reaction via a dinuclear zinc catalyst: Synthesis of either anti- or syn-α-hydroxy-β-amino ketones - Barry M. Trost (2018)
The use of imines bearing a hydrolyzable nitrogen substituent in direct asymmetric Mannich reactions with α-hydroxyketones is developed. Previous work focused on the use of N-arylimines or nonenolizable imines, and the latter with only methoxy-substituted α-hydroxyacetophenones. Using a dinuclear catalyst devised from2,6-di-(S)-2′-diphenylhydroxymethylpyrrolidino-N-methyl)-4-methylphenol and diethylzinc, a broad array of hydroxyacetylated aromatics, including phenyl, 2-furyl, 1-naphthyl, and 2-naphthyl, react well. In addition, the reactions focused on the use of enolizable imines. With the N-diphenylphosphinoyl, the reactions are anti selective with enantiomeric excesses ranging from 83 to 99%, except for the reaction of the 2-methoxy-2′-hydroxyacetylbenzene. With the N-Boc-imines, the reactions were syn selective with enantiomeric excesses from 90 to 94%. The dependence of the diastereoselectivity on the nature of the N-substituent presumably arises from the steric demands of the diphenylphosphinoyl group. Copyright © 2006 American Chemical Society.